Modern Urban Operations : Lessons Learned from Urban Opreations from 1980 to the Present (b, 2016)
Urban warfare is not a new phenomenon. The U. S. Army saw urban combat in the Revolutionary War, the War of 1812, the Civil War, and elsewhere. Starting with World War II, overall armed conflict began to occur around centers with a high population density. This new backdrop for conflict has caused a whole new set of challenge, especially in an era of public scrutiny. The "Army's capacity to engage, fight, and win major urban combat operations will determine the success of future operational and strategic endeavors".
Keywords: Guerrillas